Feedback as a poor performance remediation (2004)
The study determined the potency of feedback on remediation of students' poor performance. The design adopted in this study is the pre-test-post-test quasi-experimental control group design. Subjects were 82 fifth year (SS11) students from two secondary schools in Okene, Kogi state. Subjects in the experimental group recieved feedback. The research findings indicated that subjects in the experimental group performed significantly better than the control group in both mathematics and economics. The control group had marginal improvement. It was concluded that, provision of feedback leads to both remediation and improvement.